قیمتوں کے عدم توازن کی وجوہات: اسلامی تعلیمات کی روشنی میں ایک مطالعہ (Al-Qamar, 2020)
Islam has given the Ummah very important principles in economic teachings. If we truly embrace these teachings, and conduct our business in the light of these principles, the difficulties that have begun to manifest themselves in our economic activities with the passage of time, and seem to be growing with disproportionately great frequency and intensity, can be gradually reduced, and even eliminated. Allah almighty created human beings, and as our Creator, is aware of every particle of thought, aware of every intention, every action that we as human beings indulge ourselves in. Allah therefore has also provided us, his supreme creation, with a complete and comprehensive guide to every aspect of our lives, no matter how small or how crucial, in the teachings of Islam. And who can provide a better guide for living a successful life than the Almighty who created us and gave us life. By following the principles of Islam, we can attain welfare and prosperity in every economic aspect of our lives.  In these few phrases, we have tried to summarise these comprehensive teachings, so that their implementation can be facilitated and expedited, and they can prove to be helpful in establishing a strong economy based on Allah’s guidelines.
Keywords: Disequilibrium; Economic Principles; Welfare; Trade